EFL PRE-SERVICE TEACHERS ON THEIR ONLINE STUDENTS TEACHING - Puspa Rini, Devina Indah (RETAIN, 2021)
This study was conducted to describe how pre-service teachers prepared lesson plans, teaching methods, and assessments during online teachiong and explore the challenges of teaching English using an online system in senior high school. This study used descriptive-qualitative design and the number of EFL Pre-service teachers that was recruited as participants of the study were 5 student-teachers. Data were collected using an open-ended questionnaire and interviews through social media. The findings of this research revealed (1) Pre-service teachers developed lesson plans based on curriculum-syllabus, and internet or textbook sources. Assistance from mentor’ school was needed in making lesson plans for online teaching. However, they found it difficult to look for teaching materials, and teaching activities that are suitable for online teaching. (2) Pre-service teachers used synchronous methods using meeting platforms such as Microsoft Teams, Google Meeting, Google Classroom, and Zoom, and those platforms are applicable to use in online teaching. The main problem was technical problem such as loss of connectivity, and students’ difficulties. (3) Pre-service teachers assess their students online at every end of the meeting by asking some questions or giving assignments and submitting them online. In pre-service teacher’s difficulties, they cannot guarantee if their students did not cheat or plagiarism and students willingness to do their assignment.